A Drosophila Model of Intellectual Disability Caused by Mutations in the Histone Demethylase KDM5 - Sumaira Zamurrad (Cell Reports, 2018)
Summary: Mutations in KDM5 family histone demethylases cause intellectual disability in humans. However, the molecular mechanisms linking KDM5-regulated transcription and cognition remain unknown. Here, we establish Drosophila as a model to understand this connection by generating a fly strain harboring an allele analogous to a disease-causing missense mutation in human KDM5C (kdm5A512P). Transcriptome analysis of kdm5A512P flies revealed a striking downregulation of genes required for ribosomal assembly and function and a concomitant reduction in translation. kdm5A512P flies also showed impaired learning and/or memory. Significantly, the behavioral and transcriptional changes in kdm5A512P flies were similar to those specifically lacking demethylase activity. These data suggest that the primary defect of the KDM5A512P mutation is a loss of histone demethylase activity and reveal an unexpected role for this enzymatic function in gene activation. Because translation is critical for neuronal function, we propose that this defect contributes to the cognitive defects of kdm5A512P flies. : In humans, mutations in the transcriptional regulator KDM5 result in intellectual disability (ID). Here, Zamurrad et al. generate a Drosophila strain harboring a KDM5 mutation equivalent to an ID-associated allele to reveal a conserved role for KDM5 in cognition and an unexpected role for KDM5’s enzymatic activity in gene activation. Keywords: KDM5, Lid, H3K4me3, transcription, intellectual disability, cognition, chromatin, ribosome